Employee Recruitment Mechanism - Nurhidayah, Nita Indriani; Rahmayani, Sindy (Pascasarjana STIE Miftahul Huda, 2024)
This study examines the Islamic perspective on the employee recruitment and selection process to help companies make the right decisions in employee selection. The study was conducted using a qualitative approach with descriptive analysis, utilizing various reliable sources such as scientific publications, academic literature, and relevant online references. This study discusses several important aspects of human resource management from an Islamic perspective, including employee recruitment procedures, differences in employee status (permanent and contract), a sharia-compliant wage system, and employee competency development programs. The results of this study can be a guide for various types of companies, both those engaged in the product and service sectors, to apply Islamic values ​​in organizational management. The application of these principles is expected to encourage the creation of a workforce that is not only professionally qualified, but also has good moral integrity.